Strategi Pengembangan Penjualan online terhadap Industri Fashion - Muhammad Ridho Fadhilah; Asnita Frida B. R. Sebayang (UNISBA Press, 2023)
Abstract. Online sales are sales activities from looking for prospective buyers to offering products by utilizing the internet network which is supported by a set of electronic devices as a link to the internet network. This study discusses online sales development strategies for the fashion industry. This study aims to determine the condition of Hoya Fields online sales, identify the weaknesses and strengths of sales, find out the opportunities and threats of Hoya Fields online sales, and how the results of the SWOT strategy of Hoya Fields online sales in developing the fashion industry. Quantitative descriptive method with an analytical approach. The data used in this study were primary data obtained by distributing questionnaires to customers who had communicated with Hoya Fields. Based on the research results, there are 3 selected SO strategies, namely having loyal customer data to give compliments and facilitating the distribution of questionnaires so that Hoya Fields gets feedback from loyal customers, distributing questionnaires related to product surveys desired by consumers, with many consumers who feel the legality of branding is a decision. purchases, Hoya Fields needs to provide massive information to consumers. Abstrak. Penjualan online merupakan kegiatan penjualan dari mencari calon pembeli sampai menawarkan produk dengan memanfaatkan jaringan internet yang didukung dengan seperangkat alat elektronik sebagai penghubung dengan jaringan internet. Penelitian ini membahas terkait strategi pengembangan penjualan online terhadap industri fashion. Penelitian ini bertujuan untuk mengetahui kondisi penjualan online Hoya Fields, mengetahui kelemahan dan kekuatan penjualan, mengetahui peluang dan ancaman penjualan online Hoya Fields, serta bagaimana hasil strategi SWOT penjualan online Hoya Fields dalam mengembangkan industri fashion. Metode deskriptif kuantitatif dengan pendekatan analisis. Data yang diginakan dalam penelitian ini data primer yang didapat melalui penyebaran kuesioner terhadap customer yang sudah pernah berkomunikasi dengan pihak Hoya Fields. Berdasarkan hasil penelitan terdapat 3 strategi SO yang dipilih yaitu Memiliki data customer loyal untuk diberikan compliment dan mempermudah penyebaran kuisoner agar Hoya Fields mendapatkan feedback dari customer loyal, melakukan penyebaran kuisioner terkait survey produk yang diinginkan oleh konsumen, dengan banyaknya konsumen yang merasa legalitas branding menjadi keputusan pembelian, Hoya Fields perlu memberikan informasi yang massive kepada konsumen.